Analysis of lncRNA-Mediated ceRNA Crosstalk and Identification of Prognostic Signature in Head and Neck Squamous Cell Carcinoma - Yunbao Pan; Guohong Liu; Dujuan Wang; Yirong Li (Frontiers Media S.A., 2019)
Long non-coding RNA (lncRNA) can act as ceRNA to regulate the expression of target genes by sponging miRNAs, and therefore plays an essential role in tumor initiation and progression. However, functional roles and regulatory mechanisms of lncRNAs as ceRNAs in head and neck squamous cell carcinoma (HNSCC) remain to be determined. We downloaded RNA sequence profiles from The Cancer Genome Atlas (TCGA) database, and identified the differential RNAs by bioinformatics. Then we analyzed the biological processes of differential expressed RNAs (DER), and established their interaction networks and pathway analysis to find out potential biological effects of these DERs. Besides, we also explored the relationship between the DERs and prognosis of HNSCC patients. We obtained 525 tumor samples and 44 paracancerous controls, and there were 1081 DElncRNAs, 1889 DEmRNAs, and 145 DEmiRNAs. GO and KEGG pathways analysis of these DEmRNAs were mainly involved in "Protein digestion and absorption," "Calcium signaling pathway," and "ECM-receptor interaction." The analysis of the ceRNA network identified 61 DElncRNAs as functional ceRNAs whose dysregulated expression may affect the expression of oncogenes/tumor suppressor genes. Furthermore, univariate and multivariate Cox regression analysis revealed that 4 DElncRNAs, 3 EDmiRNAs, and 6 DEmRNAs can predict survival with high accuracy. Survival analysis found that 4 lncRNAs was related to prognostic, including overexpressed RP11-366H4.1, HOTTIP, RP11-865I6.2, and RP11-275N1.1 patients had a worse survival. In conclusion, through constructing the ceRNA network in HNSCC patients, we identified key lncRNA-miRNA-mRNA network in HNSCC. All the DERs might participate in varieties of pathways in the initiation, progression, and invasion of HNSCC. Furthermore, some miRNAs (hsa-mir-99a, hsa-mir-337, and hsa-mir-137) and mRNAs (NOSTRIN, TIMP4, GRB14, HOXB9, CELSR3, and ADGRD2) may be the prognostic genes of HNSCC. This study provided a new target and theoretical basis for further research on molecular mechanisms and biomarkers.